Understandings of social innovation within the Danish public sector: A literature review - Ada Scupola; Lars Fuglsang; Faiz Gallouj; Anne Vorre Hansen (Administrative Sciences, 2021)
Social innovation is an emerging theme within innovation theory, and so is the concept of public service innovation networks for social innovation (PSINSIs). The purpose of this article is to explore how social innovation in Danish public services is conceptualised and enacted through the lenses of public service innovation networks for social innovation. To do this, a thorough integrative review of the literature dealing with the Danish context is conducted. The Danish context is interesting in order to investigate these network arrangements, firstly because they are not well understood in the context of the Nordic welfare states, which Denmark is part of, and then because municipalities and civil society have historically had a mutually dependent relationship in Denmark. The article highlights that social innovation is framed in several ways in the Danish public sector. In particular, the results show that the literature can be grouped according to four themes: (1) samskabelse (co-creation), (2) collaboration with civil society, (3) social entrepreneurs and social innovation and (4) public-private innovation partnerships. Moreover, the article presents and discusses a number of Danish empirical projects that may be understood through the lens of the PSINSI framework. Hence, the paper contributes with new theoretical perspectives, in addition to contributing to practice.
Keywords: 350; integrative review; networks; public sector; social innovation